Integrasi nilai budaya etnis Bugis Makassar dalam proses pembelajaran sebagai salah satu strategi menghadapi era masyarakat ekonomi ASEAN (MEA) - Erman Syarif; Sumarmi Sumarmi; Ach Fatchan; I Komang Astina (Universitas Negeri Malang, 2016)
This paper aims to examine the integration of cultural values of ethnic Bugis Makassar in learning Social Geography as one of the strategies to face the Asean Economic Community (AEC). Local cultural values is an important issue that should be studied in study Social Geography. This new face is needed to adopt a variety of strategies including local cultural values in the learning process. Planting the values of the local culture in the learning process is expected to offset the influence of foreign culture that is increasingly prevalent in our society, especially South Sulawesi. Culture Bugis Makassar as one of the local culture that is growing and developing among the Bugis Makassar, has an important element that can increase the motivation of learners, namely the concept of Siri 'and Pacce. This concept when used correctly in the learning process can be a powerful incentive for students to improve their academic achievement.Keywords: Integration, Local Culture, Ethnic Bugis Makassar, Social Geography http://dx.doi.org/10.17977/um022v1i12016p013